Reconstructing National Economic Loss in Corruption Crimes - Elisabeth Sundari; Hilaire Tegnan; Muhammad Rizqi Alfarizi Ramadhan (Sekolah Tinggi Ilmu Hukum Adhyaksa, 2025)
Although various law enforcement instruments have been implemented, the handling of losses due to corruption still tends to focus on state financial losses, without considering the broader state economic losses that have a far more systemic and long-term impact. This research aims to reconstruct the elements of state economic losses to make them more operational in judicial practice, serving as a basis for fair and comprehensive recovery. The method employed is a normative juridical approach, incorporating statutory, conceptual, and case-based elements. The results of the research indicate that first, the element of state economic losses in criminal acts of corruption has not been implemented effectively due to the lack of a clear normative definition, the absence of standard quantitative parameters, and low application in judicial practice due to legal doubts and weak technical capacity of law enforcement officials. This results in the handling of losses due to corruption continuing to focus on narrow state financial losses while ignoring broader and systemic economic impacts. Second, a legal reconstruction of the element of state economic losses is necessary by strengthening the definition in Article 1 of the Corruption Law, adding characteristics and scope to the article’s explanation, and expanding the concept of confiscation and compensation to include structural losses. In addition, the implementation of alternative recovery mechanisms, such as settlement fines from the investigation stage, is important as a restorative effort that objectively considers the value of economic losses.